Cytokine reporter mice in immunological research: perspectives and lessons learned - Croxford, Andrew L (Blackwell Science Inc, 2011)
Cytokines are soluble messenger molecules with important regulatory functions throughout the immune system. ‘Cytokine reporter’ strains express marker molecules under control of elements from cytokine genes allowing for easy identification of their cellular sources. Such systems are well-accepted tools for research of cytokine function. The value of these strains lies in the ability to perform experiments relying on identification and isolation of live cytokine-expressing cells, provided that the reporter faithfully reflects the proper cytokine mRNA and protein production. As more diverse cell subsets are defined by their cytokine expression, the field has adapted with the generation of more sophisticated strains. In this review we summarize the evolution of cytokine detection methods and give examples of knowledge gained using cytokine reporter mice for cell types expressing interferon-γ and interleukin-4, -10 and -17. We also discuss current options for generating such reporter strains and their potential pitfalls.